Translocator Protein 18 kDa (TSPO): A Promising Molecular Target for Image-Guided Surgery of Solid Cancers - Hendris Wongso; Ahmad Kurniawan; Yanuar Setiadi; Crhisterra E. Kusumaningrum; Eva M. Widyasari; Teguh H.A. Wibawa; Isa Mahendra; Muhamad B. Febrian; Maula E. Sriyani; Iim Halimah; Isti Daruwati; Rudi Gunawan; et al. (Tabriz University of Medical Sciences, 2024)
The translocator protein 18-kDa (TSPO) is a mitochondrial membrane protein that is previously identified as the peripheral benzodiazepine receptor (PBR). Furthermore, it plays a significant role in a diverse range of biochemical processes, including steroidogenesis, mitochondrial cholesterol transport, cell survival and death, cell proliferation, and carcinogenesis. Several investigations also reported its roles in various types of cancers, including colorectal, brain, breast, prostate, and lung cancers, as well as melanoma. According to a previous study, the expression of TSPO was upregulated in cancer cells, which corresponds to an aggressive phenotype and/or poor prognosis. Consequently, the potential for crafting diagnostic and prognostic tools with a focus on TSPO holds great potential. In this context, several radioligands designed to target this protein have been identified, and some of the candidates have advanced to clinical trials. In recent years, the use of hybrid probes with radioactive and fluorescence molecules for image-guided surgery has exhibited promising results in animal and human studies. This indicates that the approach can serve as a valuable surgical navigator during cancer surgery. The current hybrid probes are built from various molecular platforms, including small molecules, nanoparticles, and antibodies. Although several TSPO-targeted imaging probes have been developed, their development for image-guided surgery of cancers is still limited. Therefore, this review aims to highlight recent findings on the involvement of TSPO in carcinogenesis, as well as provide a new perspective on the potential application of TSPO-targeted hybrid probes for image-guided surgery.